Android application of Throck mobile - Vidiyala, Akhila (Kansas State University, 2013)
The aim of this project is to develop an android application for managing and organizing activities of various departments in ThrockMorton building at K-State. Mobile application development is a growing trend in computer industry. With the advancements in mobile technologies and efficient 3G and 4G wireless communications, a number of desktop applications are now becoming available as mobile applications. Android has the leading market share in the entire smart phone OS available. It gives lot of space for creative development as it is open source. There are various discussion forums and official android development support websites that encourage mobile and tablet application development. The ThrockMobile application provides many features for managing inventory at ThrockMorton in Kansas State University. The features include scanning a barcode of an asset and displaying its details and can even edit any of the fields if needed. The access to this application is restricted to only those devices whose device id is existing in the database. One can request access to the application through an email client integrated with the application. Look up feature lets you look up for a user, room, ip-address and asset. Preferences module lets you enter the details of the server from which data is to be requested. This application has been tested on android devices of varying screen sizes and android OS versions. The application serves requests at an average rate of 1.5sec/request, which is above the industry average time. I mentioned in detail the reason for the above performance average times and as future enhancements I have discussed the possible solutions.
Keywords: ThrockMobile; Computer Science (0984)